THE EFFECT OF DEMONSTRATION METHOD IN TEACHING WRITING - Idrus Hamid, La Ode Muh; Jumfatriani, Jumfatriani (English Language Education Study Program, 2024)
This research presented the the effects of Demonstration Method in teaching writing at the Second Grade Students of SMP Negeri 1 Baula. The question of this research was Is there any significant effects of using the Demonstration method in teaching writing at the second-grade students of SMP Negeri 1 Baula? The objective of the research is to figure out whether there is any significant effect of demonstration method on students writing at the second grade of students in SMP Negeri 1 Baula or not. The design of this research is a quasi- experiment by using an experimental and control group with pre-test and post-test design. The variable of this research consisted of two variables, the Demonstration method as the independent variable and the students writing ability as the dependent variable. The samples are 41 students and it is taken by purposive sampling technique. The instrument of this research is a writing test. The treatment of this research is done in four meetings. Based on the result of the research, it found that the experimental class's mean is bigger (60,0) than the control class was (56,6). The result showed that T-test > Ttable (10.52>1.68). The alternative hypothesis (H1) is accepted and the null hypothesis (H0) was rejected. It could be concluded that there is a significant effect of the Demonstration Method in Teaching Writing at the Second Grade Students of SMP Negeri 1 Baula